Heritability of tea drinking and its relationship with cigarette smoking in the Chinese male adult twins. (13th January 2022) - Dongmeng, Wang; Yu'e, Xi; Wenjing, Gao; Ke, Zheng; Jun, Lv; Canqing, Yu; Shengfeng, Wang; Tao, Huang; Dianjianyi, Sun; Chunxiao, Liao; Yuanjie, Pang; Zengchang, Pang; et al.
Abstract: The aims of this study are to estimate the contributions of genetic factors to the variation of tea drinking and cigarette smoking, to examine the roles of genetic factors in their correlation and further to investigate underlying causation between them. We included 11 625 male twin pairs from the Chinese National Twin Registry (CNTR). Bivariate genetic modelling was fitted to explore the genetic influences on tea drinking, cigarette smoking and their correlation. Inference about Causation through Examination of FAmiliaL CONfounding (ICE FALCON) was further used to explore the causal relationship between them. We found that genetic factors explained 17% and 23% of the variation in tea drinking and cigarette smoking, respectively. A low phenotypic association between them was reported ( r ph = 0.21, 95% confidence interval [CI]: [0.19, 0.24]), which was partly attributed to common genetic factors ( r A = 0.45, 95% CI [0.19, 1.00]). In the ICE FALCON analysis with current smoking as the exposure, tea drinking was associated with his own (βself = 0.39, 95% CI [0.23, 0.55]) and his co‐twin's smoking status (βco‐twin = 0.25, 95% CI [0.10, 0.41]). Their association attenuated with borderline significance conditioning on his own smoking status ( p = 0.045), indicating a suggestive causal effect of smoking status on tea drinking. On the contrary, when we used tea drinking as the predictor, we found familial confounding between them only. In conclusion, both tea drinking and cigarette smoking were influenced by genetic factors, and their correlation was partly explained by common genetic factors. In addition, our finding suggests that familial confounders account for the relationship between tea drinking and cigarette smoking. And current smoking might have a causal effect on weekly tea drinking, but not vice versa. Abstract : Genetic factors explained 17% and 23% of the variation in tea drinking and cigarette smoking, respectively. A low phenotypic association between them was partly attributed to common genetic factors (rA = 0.45). In addition, our finding suggests that familial confounders account for the relationship between tea drinking and cigarette smoking and current smoking might have a causal effect on weekly tea drinking, but not vice versa.